Studies on the Effect of Baffle Plates in Settling Chamber Performance by CFD and Experimental Analysis - S. Venkatesh; R. Krishnaraj; P. M. Gopal; V. Kavimani (Journal of Applied Fluid Mechanics)
The performance of the settling chamber was examined in two scenarios in this study. In case 1, the settling chamber collection efficiency and flow characteristics were predicted without a baffle plate. In case 2, the settling chamber performance was predicted with the baffle plates. In case 2, two baffle plates were placed between the inlet and exit nozzle. The experimental set up was fabricated with the baffle plates to measure the performance. Moreover, the efficiency of the settling chamber was determined for the different inlet velocities. The Variable Frequency Drive (VFD) controller was adopted with the suction fan to vary the inlet velocity. The Reynolds Stress Model (RSM) was used to forecast the settling chamber flow characteristics. In cases 1 and 2, the best capture efficiency results were achieved at 2.5 m/s inlet velocity. The experimental study shows that the settling chamber gathering efficiency was 45% at 52.35µm. It is 44.4% higher than case 1. In CFD analysis, the settling chamber efficiency was 43%. The variation between the experimental and CFD results was 4.4%. The observations show that the pressure drop for the baffle plate setting chamber was increased 4.37 % compared to case1. The maximum settling velocity of the case 1 and case 2 chambers is 1.62 m/s and 2.81 m/s respectively. It indicates that the baffle plate chamber has highest setting velocity. Moreover, the hopper region has highest tangential velocity when introducing the baffle plate. The observations show that the radial velocity is increased in the rectangular wall region compared to hopper region due to the baffle plate.